Workload Measurement Using the Cardiovascular Load Method and Defense Research Agency Workload Scale - Kurniawan, Dicky; Akmal, Syarifah; Sayuti, Muhammad (Malikussaleh University, Aceh, Indonesia, 2024)
Workload is a collection of tasks set to be completed within a specific time. The workload can be broken down into